Conventional and supercritical fluid extraction (SFE) of colchicine from Colchicum speciosum - Bayrak, Serhat; Sokmen, Munevver; Aytac, Ezgi; Sokmen, Atalay (ELSEVIER, 2019)
This study was designed to investigate colchicine extraction from Colchicum speciosum L. using traditional and supercritical fluid extraction (SFE). The aim of this study was to i) optimize a new economical conventional liquid phase extraction procedure ii) optimize a supercritical fluid extraction (SFE) method to obtain a colchicine rich extract from C. speciosum. The seeds were defatted first and almost 7.92% oil was obtained from the extraction with 150 mL petroleum ether. The seeds were then used for both conventional and SFE extraction. The remaining solid was subjected to extraction with 95:5 methanol-water mixture (100, 150, 200, 250 and 300 mL) for 24 h by shaking the extract. The shaking process was also investigated for 1, 2, 3, 4, 5, 6 and 12 h shaking periods. The highest extract yield was obtained with 200 mL solvent. Although quantitative extract yield of 24 h was the highest (4.12%) 5, to 12 h shaking provided significant yields (approx. 3.60%). The concentration of colchicine derivatives was monitored by HPLC analysed using and presence of colchicoside, 3-demethylcolchicine and colchicine was confirmed. Colchicine content varied 0.17-0.26% depending on solvent volume and shaking period. SFE method (35 C degrees, CO2 flow rate: 1.50 mL/min., CO2 density: 0.90 g/mL, 247 bar) involving methanol modifier was investigated for 0.06, 0.2, 0.3, 0.4, 0.5 and 0.6 mL/min modifier flow rate. The extract yield was lower (1.44%) but contained only colchicine and an unknown compound which had identical DAD spectrums. 0.5 mL/min methanol modified SFE of C. speciosum seeds is highly effective for selective extraction of colchicine.
Keywords: Colchicum speciosum; Colchicine; Colchicoside; 3-demethylcolchicine; Supercritical fluid extraction (SFE); GLORIOSA-SUPERBA; AUTUMNALE; SEEDS; Agriculture